Do doctors preferring forceps encounter more obstetric anal sphincter injuries: A retrospective analysis. (29th July 2022) - Nagi, Kusam; Karantanis, Emmanuel; Mallitt, Kylie‐Ann
Abstract : Background: Obstetric anal sphincter injuries (OASIS) is a hospital‐acquired injury and can affect a woman's quality of life with problems such as anal incontinence, perineal pain, dyspareunia, mental health, psychosexual issues, and concerns about future childbirth choices. Aims: The aim of this study was to determine whether there is a correlation between a doctor's preference for instruments, their individual OASIS rate and whether factors such as their fully dilated caesarean section rate, rate of double instrumental and seniority, influences their individual rate of OASIS. Materials and methods: A population‐based retrospective cohort study was performed on 1340 term nulliparous women with singleton pregnancies who underwent an instrumental delivery or fully dilated caesarean section. A survey of doctors involved in these deliveries was performed. The risk of OASIS was analysed for maternal age, ethnicity, birth position, level of training and doctor's instrument preference using a generalised linear mixed model. Doctors' instrument preferences were established in two ways: a self‐reported survey and data‐inferred preference based on the most used instrument per doctor. The OASIS rate for individual doctors was calculated. Results: The overall risk of OASIS is higher for forceps compared to vacuum deliveries. Doctors with a preference for forceps compared to vacuum, correlated with both a lower OASIS rate and a higher fully dilated caesarean section rate. Conclusions: Doctors preferring forceps report a lower OASIS and higher fully dilated caesarean section rate. Doctors preferring vacuum must consider carefully whether forceps should follow if a vacuum fails as OASIS is more likely to occur.